Systemic quinolones and risk of acute liver failure III: A nested case–control study using a US electronic health records database. Issue 8 (31st March 2021) - Taher, Mohamed Kadry; Crispo, James A G; Fortin, Yannick; Moog, Ryan; McNair, Douglas; Bjerre, Lise M; Momoli, Franco; Mattison, Donald; Krewski, Daniel
Abstract: Background and Aim: Quinolones are globally popular antibiotics with proven potency, broad coverage, and reasonable safety. However, some concerns were raised as to their possible association with acute liver failure (ALF). The aim of this study is to assess ALF risk within 30 days of receiving a systemically administered quinolone antibiotic, in individuals with no history of liver/diseases. Methods: We conducted a nested case–control study using electronic health records from the Cerner Health Facts. The initial cohort ( n  = 35 349 943) included all patients who were admitted between 2000 and 2016, with no history of liver diseases, and had a minimum medical history of one year. Eligible cases were inpatients who were first diagnosed with ALF between 2010 and 2015. Using incidence density sampling, each case was matched with up to five unique controls by sex, race, age at index encounter, and period‐at‐risk. We used conditional logistic regression to calculate the odds ratio and 95% confidence interval for ALF risk, upon adjusting for exposure to other medications, and major confounders (diabetes mellitus and alcohol abuse). We used the STROBE Statement for reporting on our study. Results: We identified 3151 cases and 15 657 controls. Our primary analysis did not reveal an association between quinolones and ALF risk. However, some risk was identified among those with no or few comorbidities, those ≤ 60 years of age, women, men, African Americans, and Caucasians. Conclusion: Although our study does not suggest an overall association between quinolones and ALF, elevated risks seen in some subgroups warrant further investigation.